ОСОБИСТІСНО ОРІЄНТОВАНЕ НАВЧАННЯ ЯК ЧИННИК СТИМУЛЮВАННЯ ТВОРЧОЇ АКТИВНОСТІ СТУДЕНТІВ (Педагогіка вищої та середньої школи, 2022)
The article grounds the necessity of modernization of preparation of specialists on condition o f higher school. The assent is made on personally oriented teaching as the factor of stimulating creative activity o f students, their readiness to creative professional activities.